Contemporary Management of Isolated Ostial Side Branch Disease: An Evidence-based Approach to Medina 001 Bifurcations - Suleiman Suleiman; JJ Coughlan; George Touma; Richard Szirt (Interventional Cardiology: Reviews, Research, Resources)
The optimal management of bifurcation lesions has received significant interest in recent years and remains a matter of debate among the interventional cardiology community. Bifurcation lesions are encountered in approximately 21% of percutaneous coronary intervention procedures and are associated with an increased risk of major adverse cardiac events. The Medina classification has been developed in an attempt to standardise the terminology when describing bifurcation lesions. The focus of this article is on the management of the Medina 0,0,1 lesion (‘Medina 001’), an uncommon lesion encountered in <5% of all bifurcations. Technical considerations, management options and interventional techniques relating to the Medina 001 lesion are discussed. In addition, current published data supporting the various proposed interventional treatment strategies are examined in an attempt to delineate an evidence-based approach to this uncommon lesion.